Differential diagnosis between bone metastases and osteomalacia - Zakotnik, Branko (Radiology and oncology (Ljubljana), 1996)
In oncology the diagnosis of skeletal metastases is a frequent one, in infact so frequent that other diagnoses such as metabolic bone diseases affecting patients with cancer may be overlooked. In our report two cases of osteomalacia referred to an oncologist are presented; in both of them the diagnosis of diffuse bone metastases of unknown origin was suspected. The differential diagnosis is discussed and the importance of bone marrow biopsy using Yamshidi needle for diagnosis of metabolic bone disease is emphasized.
Keywords: diagnostika; kosti; medicina; metastaze; rak (medicina)